Pengukuran Kinerja SDM Metode Human Resources Scorecard sebagai Upaya Optimalisasi Kinerja Organisasi - Dwi Ermayanti (Jurnal Akuntansi dan Bisnis, 2015)
KSP Sejahtera Jatim is one of the savings and loans cooperatives. One factor that determine the achievement of the company objectives is employee performance. During this time, KSP Sejahtera Jatim in its efforts to improve the human resources quality, just assessing softskill employee performance and subjective nature. The Company has never made a comprehensive measurement of employee performance so it is unknown what factors have not been identified and has not been achieved in forming the better employee performance quality. Human Resources Scorecard is a performance measurement system of human resource that linking people, strategy and performance to produce a superior company. Human Resources Scorecard describes the vision, mission, strategy into human resources action that can be measured. Human resources performance measurement is divided into four perspectives which are financial, customer, internal business process and learning and growth perspective. Each perspective weighted by Analytical Hierarchy Process method.